AGEN KYURING ALAMI PENGGANTI NATRIUM NITRIT SINTETIS PADA KYURING DAGING SAPI - Eko Saputro; V P Bintoro; Y B Pramono (Universitas Wahid Hasyim, 2016)
The high temperature exposure on the food containing synthetic sodium nitrite (NaNO2) can cause the formation of harmful compounds of N-nitrosamine carcinogen. Nitrite (NO2-) have also been reported to react with amine in gastric acid to form N-nitrosamine. N-nitrosamine carcinogen can induce tumor in many organs of the human body. The objectives of this study were to investigate the capacity of activity of nitrate reductase (ANR) and determine the formulation of various fresh vegetables that are naturally rich in nitrate (NO3-) as a natural curing agent substitute for synthetic sodium nitrite in beef curing. Natural sources of nitrate of fresh vegetables is expected to be safer and healthier for consumption. The leaf and leaf stalks of fresh celery, fresh red spinach and fresh marigolds were separated and evaluated ANR respectively in their ability to produce nitrite during a certain incubation time. Nitrite in fresh vegetables is utilized to react to pigment beef in complex reactions series of curing. In general, the evaluation of leaf ANR showed higher than leaf stalk ANR of fresh celery and fresh red spinach. Natural nitrite that is generated by leaf of fresh celery, fresh red spinach and fresh marigolds was 0.69; 0.73 and 0.63 mg NO2-/g/h respectively. Natural curing process of beef requires incubation time which allows the conversion of nitrate to nitrite which is sufficient to produce the characteristics of naturally cured beef products similar to the conventional curing using synthetic sodium nitrite. Fresh celery leaf is recommended as a natural curing gent of beef curing because it has long been recognized by consumers more suited to a wide range of processed beef products. Natural curing of beef using fresh celery leaf is recommended as much as 22 g and incubate at room temperature for 2 hours to produce the NO2- equivalent of 30 ppm NaNO2. Key Words: natural curing, natural curing agent, activity of nitrate reductase, fresh celery leaf and beef